Solid-liquid contact TENG using a melting near-field direct writing PCL nano-fiber structure - Zhang, Shuye (2023)
Recently, the triboelectric nanogenerator (TENG) has been widely studied for the development of flexible and wearable electronics. Among the various methods for TENG modification, melting near-field direct writing is a new method to fabricate solid-liquid TENG. Here, the electrospun PCL was introduced with traditional polymers to fabricate the compound solid triboelectric layer, and water, dimethicone and GaIn were chosen as the liquid triboelectric layers. In this paper, the solid substrate effect, temperature gradient effect, and the liquid substrate effect were compared in terms of TENGs. A free-standing model of TENG is employed in this paper, and the charge generated by the PCL-PI composite solid triboelectrical solid layer is more than 10 times higher than the pristine one, showing the high charge generating ability to melt near-field direct written microfibers. Furthermore, detailed investigation will be discussed how we can get a high the out-circuit voltage and short-circuit current.